2015
DOI: 10.1016/j.landurbplan.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale assessment of metal contamination in residential soil and soil fauna: A case study in the Baltimore–Washington metropolitan region, USA

Abstract: h i g h l i g h t s• Soil contamination of metals occurred in residences located in older, more urbanized areas.• Earthworm burdens correlated with soil Pb and isopod burdens correlated with As, Cr, Ni, Pb and Zn.• Bird blood Pb correlated with earthworm Pb burdens suggesting a high risk to wildlife.• The persistence of Pb contamination in urban soils after decades of reduced emissions is alarming. a b s t r a c tThis study examined the distribution of metals in residential soils from the scale of a residentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 61 publications
(87 reference statements)
0
21
0
Order By: Relevance
“…In comparison, the heavy metal concentrations appear higher than those in other developed countries. The EFs of heavy metal, such as Cr, Ni, Cu, Zn, As, Se, Cd, and Pb, in soil of Washington in America were all below 1 (Pouyat et al 2015). While compared with the soil heavy metal concentrations in developing country, the heavy metals contents of Xiangfen County seems lower.…”
Section: Levels Of Heavy Metal Pollution In Soilsmentioning
confidence: 85%
“…In comparison, the heavy metal concentrations appear higher than those in other developed countries. The EFs of heavy metal, such as Cr, Ni, Cu, Zn, As, Se, Cd, and Pb, in soil of Washington in America were all below 1 (Pouyat et al 2015). While compared with the soil heavy metal concentrations in developing country, the heavy metals contents of Xiangfen County seems lower.…”
Section: Levels Of Heavy Metal Pollution In Soilsmentioning
confidence: 85%
“…In highly urbanized sites, heavy metal pollution is assumed traffic-derived (Pouyat et al 2010(Pouyat et al , 2015Chen et al, 2005Chen et al, , 2010Yesilonis, 2008;Figuereido et al, 2009;Trammel et al, 2011;Zhao et al, 2016). Furthermore, Kuoppamäki et al (2014) showed that metal concentrations in snow were clearly highest close to roads in the city of Lahti.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study shows that this urban-related contamination remains in wild birds, even in moderately urbanized areas. Because this contamination appears persistent even after several years, trace elements can still represent an important threat for wildlife (Pouyat et al, 2015).…”
Section: Urbanization and Trace Element Contaminationmentioning
confidence: 99%